The therapeutic effect of transcutaneous acupoint electrical stimulation combined with tongue pressure biofeedback training on dysphagia in elderly patients with ischemic stroke - Wang Xiaoying; Cheng Xiaona; Lv Xuehai; Ye Qiuya (Guoji laonian yixue zazhi)
[Objective] To observe the therapeutic effect of transcutaneous acupoint electrical stimulation combined with tongue pressure biofeedback training on dysphagia in elderly patients with ischemic stroke. [Methods] Ninety-six elderly patients with dysphagia after ischemic stroke admitted to Handan Central Hospital from July 2022 to September 2024 were selected as the study subjects. They were randomly divided into a control group and a study group (48 cases for each group) by random number table. The control group was given tongue pressure biofeedback training (46 cases were finally included), and the study group was combined with transcutaneous electrical acupoint stimulation therapy on the basis of the control group (45 cases were finally included). Functional Oral Intake Scale (FOIS) score, Swallowing Quality of Life Scale (SWAL-QOL) score, surface electromyography (sEMG) index, and cerebral hemodynamic parameters ［mean blood flow velocity (Vm) and resistance index (RI) of cerebral arteries］and the efficacy were compared between the two groups. [Results] After 2 and 4 weeks of treatment, the FOIS and SWAL-QOL scores in the two groups were higher than those before treatment (P<0.05), and the study group was higher than the control group (P<0.05). After 4 weeks of treatment: the maximum amplitude and Vm of sEMG in the two groups were greater than those before treatment (P<0.05), and the study group was greater than the control group (P<0.05); the swallowing time course in the two groups was shorter than that before treatment (P<0.05), and the study group was shorter than the control group (P<0.05); RI in the two groups was less than that before treatment (P<0.05), and the study group was less than the control group (P<0.05). After 4 weeks of treatment, the overall response rate in the study group was higher than that in the control group (P<0.05). [Conclusion] Transcutaneous acupoint electrical stimulation combined with tongue pressure biofeedback training can effectively improve sEMG and cerebral hemodynamics in elderly patients with dysphagia after ischemic stroke, prominently reduce dysphagia, and prominently ameliorate eating ability and quality of life.